2016
DOI: 10.1124/jpet.116.237743
|View full text |Cite
|
Sign up to set email alerts
|

GS-5759, a Bifunctionalβ2-Adrenoceptor Agonist and Phosphodiesterase 4 Inhibitor for Chronic Obstructive Pulmonary Disease with a Unique Mode of Action: Effects on Gene Expression in Human Airway Epithelial Cells

Abstract: (R)-6-[(3-{[4-(5-{[2-hydroxy-2-(8-hydroxy-2-oxo-1,2-dihydroquinolin-5-yl)ethyl]amino}pent-1-yn-1-yl)phenyl] carbamoyl}phenyl)sulphonyl]-4-[(3-methoxyphenyl)amino]-8-methylquinoline-3-carboxamide trifluoroacetic acid (GS-5759) is a bifunctional ligand composed of a quinolinone-containing pharmacophore [β-adrenoceptor agonist orthostere (β2A)] found in several β-adrenoceptor agonists, including indacaterol, linked covalently to a phosphodiesterase 4 (PDE4) inhibitor related to 6-[3-(dimethylcarbamoyl)benzenesulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Role of Canonical cAMP Signaling. Previous studies have established that SABA-and LABA-induced gene expression changes in BEAS-2B cells are mediated by the b 2 -adrenoceptor (Holden et al, 2014;Joshi et al, 2015Joshi et al, , 2017Kaur et al, 2008). The ability of PKIa to prevent the induction of several salmeterol-induced genes that are associated with enriched GO terms related to proinflammatory or therapeutic processes extends those findings and provides evidence that cAMP/PKA signaling is a major regulator of gene transcription.…”
Section: Discussionsupporting
confidence: 54%
“…Role of Canonical cAMP Signaling. Previous studies have established that SABA-and LABA-induced gene expression changes in BEAS-2B cells are mediated by the b 2 -adrenoceptor (Holden et al, 2014;Joshi et al, 2015Joshi et al, , 2017Kaur et al, 2008). The ability of PKIa to prevent the induction of several salmeterol-induced genes that are associated with enriched GO terms related to proinflammatory or therapeutic processes extends those findings and provides evidence that cAMP/PKA signaling is a major regulator of gene transcription.…”
Section: Discussionsupporting
confidence: 54%
“…Effect of PDE4 inhibition on gene expression changes produced by submaximal concentrations of indacaterol and formoterol. (A) BEAS-2B cells were pretreated (30 minutes) with either GSK 256066 (GSK; 10 nM) or roflumilast (Rof; 1 mM) and then exposed to either indacaterol (Ind; 1 nM) or concentration 3800Â greater than its K I for the inhibition of human PDE4B1 (Joshi et al, 2017), GSK 256066 did not affect gene expression even at a FDR ,10%. While these data suggested that genomic mechanisms play little role in the mechanism of action of PDE4 inhibitors, further analyses ascertained that GSK 256066 was a weak stimulus in BEAS-2B cells, and the small sample size used for the arrays lacked statistical power to detect small changes in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted (RNeasy Mini Kit; Qiagen Inc., Mississauga, ON, Canada) and reverse transcribed using a qscript cDNA synthesis kit according to the manufacturer's instructions (Quanta Biosciences, Gaithersburg, MD). Real-time polymerase chain reaction (PCR) analysis of cDNA was performed using the primer sequences shown in Supplemental Table 1 as described previously (Joshi et al, 2017;Yan et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GS-5759 is a bifunctional, moderately potent PDE4 inhibitor (IC 50 = 5 nM) and β 2 adrenergic agonist (EC 50 = 8 nM) made by linking a GSK256066 structurally related PDE4 inhibitor to an indacaterol structurally related β 2 -agonist (Tannheimer et al, 2014;Joshi et al, 2017). Although it has shown preclinical efficacy in a variety of species (Salmon et al, 2014) this program is assumed to be discontinued as no development has been reported.…”
Section: Gs-5759 Gileadmentioning
confidence: 99%